3D representation and analysis of enthesis morphology. Issue 3 (19th September 2013) - Noldner, Lara K.; Edgar, Heather J.H.
<x xml:space="preserve">Abstract</x> This comparison of methods for assessing the development of muscle insertion sites, or entheses, suggests that three‐dimensional (3D) quantification of enthesis morphology can produce a picture of habitual muscle use patterns in a past population that is similar to one produced by ordinal scores for describing enthesis morphology. Upper limb skeletal elements (humeri, radii, and ulnae) from a sample of 24 middle‐aged adult males from the Pottery Mound site in New Mexico were analyzed for both fibrous and fibrocartilaginous enthesis development with three different methods: ordinal scores, two‐dimensional (2D) area measurements, and 3D surface areas. The methods were compared using tests for asymmetry and correlations among variables in each quantitative data set. 2D representations of enthesis area did not agree as closely as ordinal scores and 3D surface areas did regarding which entheses were significantly asymmetrical. There was significant correlation between 3D and 2D data, but correlation coefficients were not consistently high. Intraobserver error was also assessed for the 3D method. Cronbach's alpha values fell between 0.68 and 0.73, and error rates for all entheses fell between 10% and 15%. Marginally acceptable intraobserver error and the analytic versatility of 3D images encourage further investigation of using 3D scanning technology for quantifying enthesis development. Am J Phys Anthropol 152:417–424, 2013. © 2013 Wiley Periodicals, Inc.